Simulation of Instrument Panels Production Process: Modelling a Digital Twin of the Production System and Improving the System Through DES - Narayana Shetty, Abishek; Kushalappa Koorana, Gagan Kumar (My University, 2019)
International Automotive Components (IAC) has always kept up with the advanced technologies and now aspires to simulate the production system expecting ways to improve it. A production system is very complicated due to several governing factors and planning improvement in the production is a meticulous process. With simulation, the engineers and the managers get a better picture of how a change in the production is going to affect the system. The purpose of this thesis is to help the company improve its production with the help of simulation and answer some of the "what if" questions pondered by the management. The thesis work is confined to company-specific objectives and delivers the results and reasons from the simulation. This thesis develops a Discrete Event Simulation (DES) model for production-related investigations and deriving conclusions to the ideas. The DES model is a digital twin of the factory, built using AutoMod following Jerry Bank’s methodology. AutoStat is used to simulate a scenario for several iterations considering many events within the system. Results of this study are analyzed and provided in terms of the throughput time of the products and the utilization of resources. Detecting bottlenecks and suggesting improvements has been an important activity. A general remark from the thesis is that any change in the production facility is escalated and easily comprehended using a DES tool and simulation is therefore viewed to be a very useful tool to improve a production facility.
Keywords: AutoMod, Bottlenecks, Digital Twin, DES, Jerry Banks methodology, Simulation